2013
DOI: 10.1002/adma.201302177
|View full text |Cite
|
Sign up to set email alerts
|

Highly Size‐Selective Ionically Crosslinked Multilayer Polymer Films for Light Gas Separation

Abstract: Exceptionally high hydrogen permselectivity, exceeding that of any polymeric or porous inorganic systems, is achieved using an ionically crosslinked multilayer polymer thin film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 67 publications
1
57
0
Order By: Relevance
“…PAH and PSS can form dense ionically‐crosslinked structures that compresses the thin film This densified structure imparts gas barrier. Many all‐polymer LbL films have been studied, using strong and weak polyelectrolytes, bio‐based polymers, and polyimide sheets, which all can form dense, ionically‐crosslinked structures. Yang et al found that PEI and PAA form exponentially growing, dense films with super gas barrier performance (<0.005 cm 3 m ‐2 day ‐1 atm ‐1 ) with just 8 BL .…”
Section: Layer‐by‐layer Assemblymentioning
confidence: 99%
“…PAH and PSS can form dense ionically‐crosslinked structures that compresses the thin film This densified structure imparts gas barrier. Many all‐polymer LbL films have been studied, using strong and weak polyelectrolytes, bio‐based polymers, and polyimide sheets, which all can form dense, ionically‐crosslinked structures. Yang et al found that PEI and PAA form exponentially growing, dense films with super gas barrier performance (<0.005 cm 3 m ‐2 day ‐1 atm ‐1 ) with just 8 BL .…”
Section: Layer‐by‐layer Assemblymentioning
confidence: 99%
“…The conformal nature of these coatings allows them to uniformly cover complex surfaces with varying size, shape, and porosity . LbL thin films have been produced for drug delivery, gas barrier and separation, antimicrobial behavior, and fire protection of various substrates …”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the surface of the 6 BL PEM film deposited without ATH is relatively smooth with the exception of large cracks (Fig. 3b), which are the result of the film being very glassy [48]. The ATH particles are less than one micrometer in size (Fig.…”
Section: Resultsmentioning
confidence: 95%